Analisis Campur Kode Dalam Acara Podcast Deddy Corbuzier Dengan Fiki Naki Oh Fiki Naki - Florentina Br Manurung; Lastri Marito Marbun; Jessika Caroline Harahap; Serina Angela Sitompul; Jernih Martha Banjar Nahor; Lidya Elizabeth Sihaloho; Eka Putri Saptari Wulan (Lembaga Pengembangan Kinerja Dosen, 2024)
Code mixing is a habit and role speech factor that is brought out in the use of language. There are various forms of code mixing in the interactions that occur between the narrator and the source in the podcast program. Deddy Corbuzier's program was the object, with that the research title